2012
DOI: 10.1007/s00167-012-2340-8
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis comparing bioabsorbable versus metal interference screw for adverse and clinical outcomes in anterior cruciate ligament reconstruction

Abstract: This is the first systematic review focusing on adverse effects of the BS, such as larger tunnel widening and higher rates of other complications. With these effects, routine use of the BS should be balanced with the advantages claimed. Cost-effectiveness is another issue, and well-designed RCTs are needed to better validate the implication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 48 publications
(215 reference statements)
0
23
1
1
Order By: Relevance
“…Available evidence suggests there are no long-term benefits of surgical procedures for clinical outcomes compared with conservative treatment [177, 184188, 190]. Neither was there strong evidence for a significant difference in favour of any particular surgical technique for any of the pain sites [182, 183, 189, 191]. …”
Section: Resultsmentioning
confidence: 99%
“…Available evidence suggests there are no long-term benefits of surgical procedures for clinical outcomes compared with conservative treatment [177, 184188, 190]. Neither was there strong evidence for a significant difference in favour of any particular surgical technique for any of the pain sites [182, 183, 189, 191]. …”
Section: Resultsmentioning
confidence: 99%
“…However, there have been reports of screw breakage, high rates of effusions, and decreased pull-out strength with bioabsorbable screws compared with titanium interference screws. 14 Bioabsorbable screw materials include polyglycolic acid (PGA), poly-L-lactic acid (PLLA), poly-D,L-lactic acid (PDLA), PDLA with trimethylene carbonate (TMC), PGA with TMC, PLLA with hydroxyapatite (PLLA-HA), and PLLA with b-tricalcium phosphate. In a recent metaanalysis of 11 randomized controlled studies with 878 subjects comparing bioabsorbable and metallic screws for adverse events and clinical outcomes after HT ACLR, equal short-term (2 years) and long-term (5 years) functional and clinical results were found.…”
mentioning
confidence: 99%
“…14 Larger tunnel widening on the femoral side and significantly higher rates of effusion and screw breakage were noted with the bioabsorbable screw compared with a metal screw. 14 Myers et al 18 showed that identically shaped bioabsorbable (PLLA-HA) and metallic screws were equally successful up to 2 years after 4-stranded hamstring autograft for ACLR on clinical and radiographic assessment, but MRI was not performed. Drogset et al 6 found equivalent satisfactory clinical and functional results with a PLLA screw compared with a titanium screw in bone-patellar tendon-bone ACLR at 7 years.…”
mentioning
confidence: 99%
“…In a previous biomechanical study, IFS fixation of a bone-patellar tendon-bone (BTB) graft achieved equal or superior fixation results compared with other fixation methods,1 however, to overcome the disadvantages of using traditional metallic interference screws (M-IFSs) including distorted MRIs2 and difficulty in revision surgery,3 4 the use of bioabsorbable interference screws (B-IFSs) has been reported 5. Although screw migration, tunnel widening, cyst formation and synovitis were reported as complications associated with the use of B-IFSs in long-term follow-up,5 these complications have decreased with the introduction of newer-generation B-IFSs. The newer-generation B-IFSs, which include tricalcium phosphate (ß-TCP) or hydroxyapatite (HA), have good osteoconductive properties 6.…”
Section: Introductionmentioning
confidence: 99%